2019
DOI: 10.1007/s00134-019-05520-5
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing antimicrobial therapy in the ICU: a narrative review

Abstract: The massive consumption of antibiotics in the ICU is responsible for substantial ecological side effects that promote the dissemination of multidrug-resistant bacteria (MDRB) in this environment. Strikingly, up to half of ICU patients receiving empirical antibiotic therapy have no definitively confirmed infection, while de-escalation and shortened treatment duration are insufficiently considered in those with documented sepsis, highlighting the potential benefit of implementing antibiotic stewardship programs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
175
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 195 publications
(191 citation statements)
references
References 172 publications
(195 reference statements)
1
175
0
15
Order By: Relevance
“…However, it is important to realize that RDTs are simply a tool and needs effective implementation to optimize ICU patient and stewardship outcomes. 79 Studies have consistently demonstrated a shorter time to the administration of appropriate antibiotics, as well as decreased costs, length of stay, and mortality with RDTs. A recent meta-analysis reviewed 31 studies and found that mortality risk was significantly lower with the use of RDTs compared with conventional microbiology methods, and that the number needed to treat with such systems to save one life was 20.…”
Section: Evidence In Support Of the Use Of Rdts To Optimize Antibiotimentioning
confidence: 98%
See 1 more Smart Citation
“…However, it is important to realize that RDTs are simply a tool and needs effective implementation to optimize ICU patient and stewardship outcomes. 79 Studies have consistently demonstrated a shorter time to the administration of appropriate antibiotics, as well as decreased costs, length of stay, and mortality with RDTs. A recent meta-analysis reviewed 31 studies and found that mortality risk was significantly lower with the use of RDTs compared with conventional microbiology methods, and that the number needed to treat with such systems to save one life was 20.…”
Section: Evidence In Support Of the Use Of Rdts To Optimize Antibiotimentioning
confidence: 98%
“…[88][89][90] Currently, the greatest challenge to ICU clinicians is effective management of multidrug-resistant GNB infections. 79 IIAT of serious GNB infections is associated with increased mortality and has been the rationale for using broad-spectrum antibiotics upfront in critically ill patients. 32,46,[91][92][93] RDTs along with ASPs have been particularly effective in improving outcomes for these infections.…”
Section: Evidence In Support Of the Use Of Rdts To Optimize Antibiotimentioning
confidence: 99%
“…However, even very short exposure (1 to 3 days) to carbapenem is associated with a 5-fold higher risk of emergence of imipenem-resistant Gram-negative bacteria in the intestinal microbiota of ICU patients. 10 Intensivists are thus confronted with a permanent dilemma between the initiation of adequate antibiotic therapy and the risk of increasing MDR bacteria 3,11 by the prescription of broad-spectrum antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…However, even very short exposure (1 to 3 days) to carbapenem is associated with a 5-fold higher risk of emergence of imipenem-resistant Gramnegative bacteria in the intestinal microbiota of ICU patients. 10 Intensivists are thus confronted with a permanent dilemma between the initiation of adequate antibiotic therapy and the risk of increasing MDR bacteria 3,11 by the prescription of broad-spectrum antibiotics.…”
Section: Introductionmentioning
confidence: 99%